2012
DOI: 10.2166/wst.2012.099
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of nutrients and related environmental factors on distribution and size structure of Noctiluca scintillans populations of the Eutrophic Tha Chin Estuary, Thailand

Abstract: This study aimed to analyze the impacts of nutrients and related aquatic factors on changes in the Noctiluca population of the Tha Chin estuary, a nutrient-rich estuary located in the inner Gulf of Thailand. Field surveys were carried out at 30 stations during November 2009 to August 2010. The results indicated high levels of dissolved inorganic nitrogen (DIN; 13.89-46.99 μmol/L) and PO(4)(3-)-P (0.20-3.05 μmol/L) where the Noctiluca red tide occurred, particularly during the high-loading period. Dense populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Moreover, our findings showed that DN>60% blooms occurred mainly in estuaries and closer to the shore, which were more highly influenced by freshwater discharge than green Noctiluca blooms. This finding is consistent with the preferred salinity range of dinoflagellates such as Ceratium furca (12-27 psu) and green Noctiluca (22-33 psu) (Lirdwitayaprasit et al, 2006), as well as the correlation between high salinity (25-29 psu) and green Noctiluca abundance reported by Chuenniyom et al (2012). Thus, our results suggest that, in addition to contributing anthropogenic nutrients, river discharge may influence red tide distributions by regulating salinity levels.…”
Section: Seasonal Variability Of Green Noctiluca and Other Red Tidessupporting
confidence: 92%
See 3 more Smart Citations
“…Moreover, our findings showed that DN>60% blooms occurred mainly in estuaries and closer to the shore, which were more highly influenced by freshwater discharge than green Noctiluca blooms. This finding is consistent with the preferred salinity range of dinoflagellates such as Ceratium furca (12-27 psu) and green Noctiluca (22-33 psu) (Lirdwitayaprasit et al, 2006), as well as the correlation between high salinity (25-29 psu) and green Noctiluca abundance reported by Chuenniyom et al (2012). Thus, our results suggest that, in addition to contributing anthropogenic nutrients, river discharge may influence red tide distributions by regulating salinity levels.…”
Section: Seasonal Variability Of Green Noctiluca and Other Red Tidessupporting
confidence: 92%
“…Seasonal variability may result from the interaction between increased river discharge into the northern uGoT and the transfer of riverine nutrient inputs by eastward circulation generated by the monsoon along the northern coast (Buranapratheprat et al, 2002;Buranapratheprat et al, 2006;Yu et al, 2018). Chuenniyom et al (2012) examined the green Noctiluca population in the Tha Chin estuary (off the north coast of Thailand) and observed a dense population in the outer part of the estuary with relatively high salinity, as well as a red tide during the high loading period of river discharge from November to December 2009. Moreover, ammonium nitrogen and dissolved inorganic nitrogen concentrations influence the total green Noctiluca population density, whereas orthophosphate phosphorus regulates the development of green Noctiluca red tides (Chuenniyom et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations